Uji Aktivitas Antimikroba Ekstrak Etanol Daun Cayratia trifolia terhadap Staphylococcus aureus dan Candida albicans - Sari, Rizki Sari Endah; Soegianto, Lisa; Hermanu, Liliek S, (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Cayratia trifolia is a wild plant that is easily found in the lowlands, tropical and subtropical regions. Cayratia trifolia is known to be efficacious as an antibacterial, antifungal, antiprotozoa, hypoglycemia, anticancer and diuretic. This study aims to determine whether the ethanol extract of Cayratia trifolia leaves has antimicrobial activity against Candida albicans and Staphylococcus aureus using well diffusion method; to determine the value of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using microdilution method; and to determine the secondary metabolite groups which have antimicrobial activity against Staphylococcus aureus and Candida albicans. In this study bioautography method was carried out to determine the secondary metabolite group that can inhibit microbial growth. Ethanol extract of Cayratia trifolia (Galing-galing) leaves has no antimicrobial activity against Candida albicans. The MIC value of the ethanol extract of Cayratia trifolia (Galing-galing) leaves against Staphylococcus aureus is at a concentration of 125 ppm, while the MBCvalue is at a concentration of 250 ppm. The group of compounds that have antibacterial activity against Staphylococcus aureus is polyphenol, meanwhile flavonoid suspected has activity against Candida albicans.